A conceptual analysis of virtual supply chain collaborative network. (2nd January 2015) - Toh, Albert K.; Zhang, Qingyu
For many modern enterprises, supply chains have become one of the core business processes involving interorganisational relationships and coordinated activities across enterprise boundaries. B2B collaboration between trading partners has contributed to strategic and operational advantages. Organisations may collaborate across supply chain processes ranging from information exchange, coordination, cooperation, to close collaboration. The present paper systematically reviews literature on supply chain collaboration, interorganisational relationship, information systems and organisational design. Changing patterns of organisational forms and governance from extended enterprise to network and virtual organisations are discussed in relation to inter-organisational collaboration. A socio-technical approach is presented to conceptualise and analyse supply chain collaboration in virtual network organisation. Based on a critical analysis and synthesis of the literature, some design principles and future research directions are proposed. Inter-organisational information systems for virtual supply chain and collaborative network organisation are promising areas of research that this paper seeks to advance.